Optic neuropathy in sheep associated with overdosage of closantel - Secorun Borges, Alexandre [UNESP]; Nogueria Mendes, Luiz Claudio [UNESP]; Lima de Andrade, Alexandre [UNESP]; Machado, Gisele Fabrino [UNESP]; Peiró, Juliana Regina [UNESP] (My University, 1999)
This report describes clinical and pathological findings in 2 flocks in Brazil where blindness and deaths in sheep occurred after closantel overdosage. Depression, weakness, and blindness affected 37 animals and 17 died in 2 flocks of 190 animals. Two animals submitted for ophthalmic examination showed no inflammation in the anterior segment of both eyes; posterior segment evaluation by indirect ophthalmoscopy suggested retinal degeneration. One postmortem evaluation local spongy vacuolization was in several regions of the brain and the optical nerves had severe axonal degeneration.
Keywords: closantel; animal experiment; blindness; clinical feature; depression; drug overdose; nerve degeneration; nonhuman; optic nerve disease; retina degeneration; sheep; Animals; Anthelmintics; Blindness; Brazil; Nerve Degeneration; Optic Nerve; Optic Nerve Diseases; Overdose; Retinal Degeneration; Salicylanilides; Sheep; Sheep Diseases